2011
DOI: 10.1021/ed1005745
|View full text |Cite
|
Sign up to set email alerts
|

Managing Laboratory Data Using Cloud Computing as an Organizational Tool

Abstract: One of the most significant difficulties encountered when directing undergraduate research and developing new laboratory experiments is how to efficiently manage the data generated by a number of students. Cloud computing, where both software and computer files reside online, offers a solution to this data-management problem and allows researchers to coordinate their efforts just as easily whether they are working in the same laboratory or laboratories halfway around the world. This article discusses the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
(12 reference statements)
0
32
0
Order By: Relevance
“…Cloud computing tools (e.g. Google Docs) also provide a solution to data-management problems and enable users to coordinate efforts (Bennett & Pence, 2011).…”
Section: Cloud Computing For Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud computing tools (e.g. Google Docs) also provide a solution to data-management problems and enable users to coordinate efforts (Bennett & Pence, 2011).…”
Section: Cloud Computing For Collaborationmentioning
confidence: 99%
“…G suite for Education, Google Drive, Docs, Slides, and Sheets) are particularly useful. Studies on the use of Google applications have indicated that students prefer discussion and collaboration, have positive attitudes towards collaborative platforms, and interact effectively in group projects and that these platforms positively influence intention (Bennett & Pence, 2011;Deton, 2012;Huang, 2017). Studies showed that the application of technology (Al-Samarraie & Saeed, 2018) and the jigsaw method (van…”
Section: Introductionmentioning
confidence: 99%
“…There is growing consensus that cloud computing tools offer more cost-effective options for educators who are able to gain expanded access to research and collaborative opportunities that leverage high-performing technology infrastructure, despite limited resources (Gonzalez-Martinez et al, 2015; Sabi et al, 2016). This consensus is reinforced by findings that the specific cloud computing tools that form the foundation of the KMS-BI (Google Forms, Google Sheets, and Microsoft OneDrive) are already used broadly in education settings (Gonzalez-Martinez et al, 2015) for a variety of applications (e.g., see Bennett & Pence, 2011; Bonham, 2011; Herrick, 2009; Nevin, 2009; Sultan, 2010).…”
Section: Moving From Exploration To Full Implementation Of Data-basedmentioning
confidence: 99%
“…Cloud computing allows students to work on individual projects independently but report their results in a way that makes it easier for an instructor to keep track of them. Bennett and Pence have used the cloud in this way to manage the data from an undergraduate laboratory or research [6].…”
Section: Cloud Computing and Artificial Intelligencementioning
confidence: 99%